High Serum Estradiol Reduces Acute Hepatotoxicity Risk Induced by Epirubicin Plus Cyclophosphamide Chemotherapy in Premenopausal Women with Breast Cancer - Huang, Shunmin; Liu, Maobai; Fu, Fangmeng; Liu, Hangmin; He, Baochang; Xiao, Danni; Yang, Jing (Frontiers in Pharmacology, 2021)
Aim: We evaluated whether acute drug-induced liver injury (DILI) caused by adjuvant chemotherapy with epirubicin plus cyclophosphamide for early breast cancer was associated with estradiol (E2), luteinizing hormone (LH), and follicle-stimulating hormone (FSH). Methods: Reproductive hormone test results of breast cancer patients were collected in the first chemotherapy cycle. E2, LH, and FSH levels were loge-transformed to normally distributed variables and were assessed using Student’s t-test to determine significant differences between the case and control groups. Hormone levels were classified according to the interquartile range and analyzed by logistic regression to determine their association with DILI caused by chemotherapy. Results: Among the 915 enrolled patients (DILI group: 204; control group: 711), menopausal status, along with serum E2, LH, and FSH levels, did not substantially differ between case and control groups. However, in the premenopause subgroup (n = 483), we found a significant difference in the E2 level between the case and control groups (P = 0.001). After adjusting for age and body mass index, premenopausal patients with 152–2813 pg/mL E2 showed a lower risk of chemotherapy-induced DILI than patients with ≤ 20 pg/mL E2 (odds ratio: 0.394; 95% confidence interval: 0.207–0.748). The linear trend χ2 test revealed that E2 levels in premenopausal patients with breast cancer were inversely associated with the development of DILI. Conclusion: High serum E2 levels are associated with a reduced DILI risk in premenopausal patients with breast cancer undergoing epirubicin plus cyclophosphamide adjuvant chemotherapy.